Diclofenac Degradation by Immobilized Chlamydomonas reinhardtii and Scenedesmus obliquus - Thamali Kariyawasam; Martin Petkovich; Bas Vriens (MicrobiologyOpen)
ABSTRACT Diclofenac (DCF), a commonly used anti‐inflammatory medication, presents environmental concerns due to its presence in water bodies, resistance to conventional wastewater treatment methods, and detection at increasing concentrations (ng/L to µg/L) that highlight DCF as a global emerging pollutant. While microalgae have been effective in degrading DCF in wastewater, immobilization into a matrix offers a promising approach to enhance treatment retention and efficiency. This study aimed to evaluate the efficacy of DCF removal using immobilized freshwater microalgae. Two algal species, Chlamydomonas reinhardtii (Chlamydomonas) and Scenedesmus obliquus (Scenedesmus), were tested for 6 days in both free and immobilized forms to determine if immobilized algae could degrade DCF comparably to free cells. The findings indicate that by Day 3, immobilized Chlamydomonas and Scenedesmus removed 78.0% and 80.1% of DCF, outperforming free‐cell cultures. Mixed cultures demonstrated synergistic effects, with removal amounts of 91.4% for free and 92.3% for immobilized systems. By Day 6, all conditions achieved complete DCF removal (100%). Mechanistic analysis showed 80.0% biodegradation and 20.0% bioaccumulation in free Chlamydomonas and 56.8% biodegradation with 43.2% bioaccumulation in Scenedesmus. Immobilization shifted pathways slightly: in Chlamydomonas, 61.6% of DCF removal occurred via biodegradation, 18.3% via bioaccumulation, and 20.1% via abiotic degradation. For Scenedesmus, immobilization achieved 45.6% biodegradation, 36.6% bioaccumulation, and 17.8% abiotic degradation, enhancing abiotic degradation while maintaining biodegradation efficiency. This research serves as a proof of concept for utilizing immobilized algae in DCF removal and suggests an avenue for improved wastewater treatment of emerging contaminants.